NAFLD and Physical Exercise: Ready, Steady, Go! - Cigrovski Berkovic, Maja; Bilic-Curcic, Ines; Mrzljak, Anna; Cigrovski, Vjekoslav (Frontiers in Nutrition, 2021)
Along with the increase in obesity and type 2 diabetes, the non-alcoholic fatty liver disease (NAFLD) incidence is escalating, thus becoming a leading cause of liver cirrhosis and a significant burden of liver-related outcomes. Since there is no pharmacotherapy available to address the NAFLD, the most effective solutions seem to be lifestyle changes centered on physical activity. Exercise could mediate its beneficial effects directly on the liver and indirectly via extrahepatic pathways, forming a dose-response relationship with NAFLD in terms of prevalence and disease severity. Health-enhancing physical activity (HEPA) levels are mainly needed to exert beneficial effects in obese subjects, while even a small amount of exercise can be beneficial for lean individuals to prevent NAFLD. This mini-review addresses three major points regarding physical activity and NAFLD: prevention, treatment, and extrahepatic benefits, offering recommendations on type and intensity of exercise in liver disease.